Patterns of Patient Recruitment in Clinical Studies on the Example of International Multicenter Clinical Studies (IMCTs) - S. S. Milovanov (Разработка и регистрация лекарственных средств, 2023)
Introduction. Patient recruitment is one of the main quantitative and qualitative characteristics of a clinical trial. As a quantitative characteristic, the recruitment of patients is, first of all, the final figure necessary to answer the researcher's question; as a qualitative characteristic, the recruitment of patients is a process subject to influence. The recruitment of patients in the center is determined by the rate per month and allows you to gain the statistical power of the protocol, and if the recruitment of patients does not reach the planned capacity, then the capacity may not be gained and this leads to the failure of the clinical trial. Failures in patient recruitment reported in the literature lead to more than 80 % of failed clinical trials of all phases. Patient recruitment as a process is influenced by various factors, and the authors identify recruitment predictors, recruitment facilitators, and barriers to patient recruitment.Aim. To consider the general features and patterns of recruitment of patients in clinical trials on the example of international multicenter clinical trials.Materials and methods. We analyzed the quantitative characteristics of patient recruitment in 4 clinical trials with successful recruitment.Results and discussion. Despite the uniqueness of each protocol, the set of patients has its own patterns common to all clinical studies. It was studied, in particular, that the integrative assessment of the preliminary recruitment of patients by the researcher of the clinical center is not associated with an objective pool of patients and affects the rate of patient recruitment and targeted patient recruitment. We found that the number of clinical centers not recruiting patients in each study is at least 30 % of all centers involved. Three patient recruitment rates have also been identified that need to be considered when planning a clinical trial.Conclusion. We have identified patterns in patient recruitment that will help in planning clinical trials.